Global trends and hotspots in macrophage research related to hypertension from 2015-2024: bibliometric research and visualization analysis - Wang, Xuefei; Chai, Yemao; Dou, Ye; Li, Xinyi; Li, Fanghe; Gao, Kuo (Frontiers in Immunology, 2025)
BackgroundHypertension continues to be a global health and economic burden, conventionally characterized by a chronic inflammatory state. Macrophages are critical for the initiation, progression and manifestation of hypertension. As studies on the relationship between macrophages and hypertension increase substantially, identifying critical research areas and unraveling potential interaction mechanisms become increasingly essential.MethodsArticles associated with hypertension and macrophages in recent 10 years were retrieved from the Web of Science Core Collection for analysis, using Microsoft Excel, VOSviewer, CiteSpace and Scimago Graphica.ResultsAfter excluding studies that did not meet inclusive standard based on time (2015-2024) and type (article or reviews), 2,013 original articles related to macrophages associated with hypertension were included. The number of publications has been increasing annually. These records consisted of 2,013 English language papers published in 351 journals by 315 institutions or regions from 83 countries/regions between 2015 and 2024. We analyzed the co-cited references clusters to objectively outline the current state of research, including the regulatory mechanisms of hypertension, diseases related to hypertension, and the lifestyle factor. Inflammation remains one of the most popular research hot-spot. The most popular publishing journal in this field is PLOS ONE and the most prolific writer is Li, Hui-Hua. The primary keywords cluster in this field is inflammation, with the highest occurrences and TLS among the top 10 keywords.ConclusionThese comprehensive and visualized bibliometric results summarized the significant findings in macrophage-related hypertension studies over the past 10 years. Macrophages appear to be effective in the treatment of hypertension as potential targets, but further research is needed to clarify the specific pathophysiological mechanisms involved.